2022
DOI: 10.1186/s13567-022-01053-w
|View full text |Cite
|
Sign up to set email alerts
|

Current knowledge on epidemiology and evolution of novel porcine circovirus 4

Abstract: Porcine circovirus type 4 (PCV4) is a newly emerging virus, with both PCV4 genomic DNA and specific antibodies detected in swine herds in several provinces in China and South Korea. Although the virus was first identified in 2019 in Hunan, China, retrospective research suggests that serum samples collected as early as 2008 were positive for PCV4 antibody. Infections with only PCV4 or co-infections with other pathogens have been associated with several clinical manifestations, but its pathogenesis remains to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 29 publications
1
30
0
Order By: Relevance
“…Animal circoviruses, such as porcine circoviruses (PCV) 1–4, have been responsible for reproductive failure, dermatitis, nephropathy, and respiratory diseases in animals ( 17 , 18 ), manifestations not found in the case we report. However, PCV2 associated with cases of jaundice in pigs ( 19 – 21 ) and hepatitis in a horse have been demonstrated ( 22 ).…”
Section: Discussionmentioning
confidence: 50%
“…Animal circoviruses, such as porcine circoviruses (PCV) 1–4, have been responsible for reproductive failure, dermatitis, nephropathy, and respiratory diseases in animals ( 17 , 18 ), manifestations not found in the case we report. However, PCV2 associated with cases of jaundice in pigs ( 19 – 21 ) and hepatitis in a horse have been demonstrated ( 22 ).…”
Section: Discussionmentioning
confidence: 50%
“…Further investigation is required www.nature.com/scientificreports/ to establish the standardized criteria for genotyping PCV4, given the current paucity of sequence information. As mentioned above, previous reports showed that the amino acid at the position 27 of the Cap gene could be used as a marker to distinguish between PCV4a (27S) and PCV4b (27N) 19,20 . However, the results in this study showed that the amino acid residue at position 27 cannot be used to differentiate between PCV4a and PCV4b since the Thai PCV4b strains and the Korean PCV4b strains (KU-02010 and KU-02011) showed N27S (Fig.…”
Section: Genetic Characteristics Of Pcv4mentioning
confidence: 90%
“…This is in contrast with PCV2 genotyping that a unified classification scheme based on Cap gene was proposed 18 . For PCV4 genotyping, there have been several studies proposing different criteria and markers to differentiate PCV4 genotypes, such as 2-group classification (PCV4a and PCV4b) and 3-group classification (PCV4a, PCV4b, and PCV4c) 10,[19][20][21] . Among these studies, the residue at 27 and 212 of capsid gene were also proposed to be used in distinguishing PCV4a (27S and 212L) from PCV4b (27N and 212M) 19,20 .…”
Section: Genetic Characteristics Of Pcv4mentioning
confidence: 99%
See 1 more Smart Citation
“…The multiple disease syndromes are ascribable to PCV2 infection and are summarized under the term of porcine circovirus diseases (PCVD) (Palinski et al, 2017). Recently, novel types of PCV has been identified, including PCV3 (Klaumann et al, 2018;Saporiti et al, 2021) and PCV4 (Li et al, 2022;Wang et al, 2022). It is currently under surveillance for its impact on swine industry.…”
Section: Introductionmentioning
confidence: 99%